In-pixel autoexposure CMOS APS. - Yadid-Pecht, O. (IEEE Journal of solid state circuits)
A CMOS active pixel sensor (APS) with in-pixel autoexposure and a wide dynamic-range linear output is described. The chip features a unique architecture enabling a customized number of additional bits per pixel per readout, with minimal effect on the sensor spatial or temporal resolution. By utilizing multiple readouts via real-time feedback, each pixel in the field of view can automatically set an independent exposure time, according to its illumination. A customized, large increase in the dynamic range can be achieved and a scene containing both bright and dark regions can be captured. A prototype of 64 × 64 pixels has been fabricated using 1-poly 3-metal CMOS 0.5 μm n-well process available through MOSIS. Power dissipation is 3.7 mW at VDD = 5 V. The special functions have been verified experimentally, and an increase of 2 bits over the inherent dynamic range captured is shown.